Development of a Novel Humidifier for Air Breathing Devices - Brizio, Pablo Joaquin (Auckland University of Technology, 2011)
Continuous positive pressure of air on the airways (CPAP) is the most common treatment for the obstructive sleep apnea syndrome. Humidification of the air applied to the patient improves patient compliance by preventing congestion and nasal and throat dryness. Most humidifiers used in CPAP systems are traditional heating-type humidifiers which consume large amount of energy. In this thesis, a non-traditional humidification technique was developed to be used in various respiratory supportive device applications such as CPAP therapy. Atomization processes were reviewed and ultrasonic atomizers were found to be the most suitable in terms of power consumption, droplets size distribution of the spray generated and size of the device. Four setups were used for experiments with these atomizers using five frequencies (1.5, 1.7, 2.1, 2.6 and 3.0 MHz). The experiments demonstrated that excitation with sine pulses has better efficiency than square pulses. In order to avoid overheating of the ultrasonic atomizer, the pulses must be sent in bursts and the frequency at which this bursts are sent (duty cycle) was proportional to the heating of the transducer. The droplet size distribution was measured by three different methods (photographic, impact and optic) and it did not have a significant change with the power applied to the transducer. The power did have a direct relationship with the atomization rate. Ultrasonic transducers with resonant frequency of 1.5 MHz are recommended for this application since the generated droplets have a small diameter (which facilitates its evaporation). The complexity of a driving circuit also increases with the frequency. Ideally there should be no water droplets in the air supplied to the patient. The evaporation of the droplets was mathematically modelled and experimentally tested to determine if the air that will be supplied needs to be heated to reach the fully evaporation. With an airflow rate of 60 L/min, the full evaporation of the droplets was reached in a relatively short distance (0.05 m) compared with the normal separation between the equipment and the patient (1.50m). There is no need to use a heater achieve such evaporation of the droplets. In this device, the pathogen risk could be reduced with the use of hydrophobic filters. This work demonstrates that ultrasonic transducers are capable of atomizing sufficient quantities of water for this application with low power consumption.
Keywords: Novel humidifier; Air breathing devices; Continuous positive pressure of air on the airways (CPAP)